Fiscal and monetary anomie in Argentina: The legacy of endemic populism - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
Argentina's modern economic history offers perhaps the clearest evidence in support of a rules-based fiscal and monetary policy framework. From 1899 until 1914 the country abided by the rules of the gold standard and experienced rapid GDP growth with price stability. After WWI and until 1939, when it was mostly off the gold standard, its inflation rate and fiscal balances remained in line with those of the world's most developed countries. During the 1930s the Argentine Treasury was able to issue long-term debt in pesos at rates between 3% and 4% per annum. Something fundamental happened after 1945 and its effects proved persistent: since then inflation has averaged 143% a year - with several bouts of extreme inflation and hyperinflation. In the last 50 years, persistent and high fiscal imbalances, low growth and recurrent sovereign debt defaults have become semi-permanent features of the Argentine economy. This paper argues that Argentina suffers from a condition that can be described as fiscal and monetary anomie, the roots of which can be traced back to the establishment of a populist-corporatist economic regime in 1946. It also contends that the failure of the 1990s structural reforms reinforced this condition.
Keywords: E5; E63; N16; O54; 330; Argentina; Economic History; Fiscal Policy; Monetary Policy; Populism